Sensible air cool-warm fan with thermoelectric module systems development. (March 2019) - Wiriyasart, S.; Naphon, P.; Hommalee, C.
Abstract: An experimental investigation on the application of thermoelectric modules for cooling and heating supply air of the conventional fan system is performed. The thermoelectric cooling module is comprised of six thermoelectric plates, two cold water boxes and a hot water box. While the thermoelectric heating module is comprised of three thermoelectric plate, a cold and hot water boxes. The obtained results from the heating capacity of the sensible air cool-warm fan system are presented and compared with those from the conventional fan system (without thermoelectric module). It can be found that the minimum and maximum water temperature obtained from the thermoelectric module are 12 °C and 70 °C, respectively. For on-off modes every 5 min, average cool air obtained from the fan system with thermoelectric module is 2.0 °C lower than that without thermoelectric module while average warm air temperature is 2.5 °C higher than that without thermoelectric module. The obtained results are also expected to guideline that will allow designing and developing the sensible air cool-warm fan system with thermoelectric module system to higher thermal performance.